Hubungan Pemberian Motivasi Orang Tua dengan Hasil Belajar Matematika Siswa Kelas V SD Gugus XVIII - Fitri Nandasari; Makmur Nurdin; Rosmalah Rosmalah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The problem in this study is the lack of parental motivation for student learning outcomes which makes students have no desire to learn.  This study is a quantitative study with a correlation design that aims to determine the relationship between parental motivation and learning outcomes in mathematics for fifth grade elementary school students, cluster XVIII.  Based on the results of inferential statistical analysis, the value of tcount () is greater (>) the value of ttable (1.67252) at a significance level of 5%.  Thus H0 is rejected and H1 is accepted.  Based on the analysis above, it can be concluded that giving parents motivation has an impact on students' enthusiasm for learning in participating in the learning process so that they can improve their learning outcomes.  From these conclusions, the impact of this study is known that the provision of high parental motivation can improve student learning outcomes.